An analysis of financial performance for Mutiara Smart Computing Sdn Bhd from year 2004 to 2008 / Nor Aslinda Allias - Allias, Nor Aslinda (Faculty of Business and Management, 2010)
This paper study about the financial performance of Mutiara Smart Computing Sdn Bhd. This study will focus on the company yearly financial statement analysis from year 2004to year 2008. A rough idea on the performance of a company can be obtain by looking at its company financial statement analysis. However, there is a need for reliable information in which every party can use for better decision making and to enhance the understanding over an organization’s actual business performance, and not just based on assumptions or an idea over a particular situation. For this reason, researcher will conduct a thorough ratio analysis to analyze the annual statement analysis statement that meet the organization’s goals, to identify the limitation in gained and utilized the funds that affect the profitability of the company.